Pengaruh Green Entrepreneurial Orientation Terhadap Sustainable Innovation Performance dengan Mediasi Green Innovation Culture pada UMKM di Yogyakarta - Naufal Beni Purnama; Siti Nursyamsiah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Environmental sustainability has become a major concern for businesses, particularly MSMEs, to adopt environmentally friendly business practices. This study aims to analyze the influence of Green Entrepreneurial Orientation (GEO) on Sustainable Innovation Performance (SIP), with Green Innovation Culture (GIC) as a mediator in MSMEs in the Yogyakarta region. This study used a quantitative approach, with data collected from 200 MSMEs from various business sectors using a structured questionnaire. Data testing was conducted using SEM-PLS. The results showed that GEO had a positive and significant effect on SIP with a p-value of 0.000 and GIC with a p-value of 0.000. Furthermore, GIC was shown to positively mediate the relationship between GEO and SIP with a p-value of 0.002. These findings emphasize the importance of implementing GIC for MSMEs in strengthening the role of GEO in achieving MSME SIP, while also contributing theoretically.